(untitled) (Swiss Medical Weekly, 2019)
OBJECTIVE About 50% of acute coronary syndromes occur in patients classified as being at low coronary risk. We aimed to assess the potential preventive benefit of carotid plaque imaging with ultrasound. METHODS We assessed the prevalence of “old” arteries (vascular age ≥70 years; VA70) in 3248 healthy subjects aged 40–65 years from the Swiss region of Olten and the German region of Koblenz. We compared sensitivity, specificity and discriminatory performance of SCORE, PROCAM and AGLA coronary risk calculators to detect VA70 for various decision thresholds and performed reclassification and cost-efficiency analysis. RESULTS VA70 was found in one out of eight subjects. Sensitivity for VA70 was 6% at the 10% AGLA threshold in women and 30% in men in the Olten area, which was confirmed for the Koblenz area with PROCAM (sensitivity 8% in women, 56% in men). Results were similar for SCORE. The discriminatory performance ranged between 0.69 and 0.82. Reclassification from low risk to a higher risk category occurred in 17–35% of patients. Analysis showed that carotid imaging for CHF 100 per person was highly cost efficient. CONCLUSIONS In subjects aged 40–65 years, the prevalence of old arteries is one out of eight and the detection rate of AGLA and SCORE is lower in women (6% for PROCAM) than for men (30%) at the 10% threshold. Carotid imaging may be used to reclassify subjects from low to intermediate or high cardiovascular risk. Our method is highly cost efficient at a price of CHF 100 per examination.